Aquatic insects : challenges to populations : proceedings of the Royal Entomological Society's 24th symposium (CABI, 2008)
This book considers some of the potential influences on individuals and populations (e.g. environmental stresses, parasites, cannibalism, dispersal limitations), the 'cunning tricks' used by aquatic insects to overcome challenges (e.g. polarization vision, life-history strategies, osmoregulation, cold hardiness) and the consequences of those challenges at different levels of organization (e.g. distribution patterns, population structure, population genetics, evolution).